Effect of premature infant oral motor intervention on oral feeding and weight gain: A Systematic review and meta-analysis - Jyoti; S Malar Kodi; Rupinder Deol (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: Sucking and swallowing coordination did not achieve until 32–34 weeks of gestation in premature infants. Oral motor stimulations improve oral motor musculature and neurobehavioral synergism which improves the rate of oral feeding readiness and weight gain and ultimately reduces the duration of hospitalization. Premature Infant Oral Motor Interventions (PIOMI) is a specific oral motor therapy effective in improving the clinical outcomes among premature infants. Earlier no review had been conducted specifically to assess the effectiveness of PIOMI on oral feeding progression, weight gain, and Length of hospital Stay (LOS) among premature infants. So, the present review had been planned. Materials and Methods: Review was conducted by searching databases like PubMed/Medline, Embase, Ovid, Clinical Key and Academia, Google and Google Scholar (from PIOMI inception to October 2020). Published articles on RCTs and clinical trials were included. Results: Six studies, with a total of 301 premature infants, were included in Meta Analysis (MA). PIOMI was found effective in early attainment of feeding progression (Mean Difference (MD) = −4.63 days at 95% Confidence Interval (CI) = −4.97 to − 4.29, p < 0.001) and shifting from gavage to independent oral feeding (MD = −2.54 days at 95% CI = −3.13 to − 1.95, p < 0.001), shows weight gain at discharge (MD = 51.61 grams at 95% CI = 19.84 to 83.38, p = 0.001), and reduces LOS (MD = −2.81 days at 95% CI = −3.51 to − 2.10, p < 0.001). Conclusions: Review shows shows the effectiveness of PIOMI in improving oral feeding progression and early attainment of gavage to independent oral feedings, and it also showed weight gain at discharge and reduced LOS.